Transtorno do desenvolvimento da coordenação em crianças de 7 anos de idade matriculadas em escolas públicas do município de Araraquara-SP - Jóia, Andressa Fernanda (2014)
The Developmental Coordination Disorder - DCD occurs when there is delayed development of motor skills or difficulty in motor coordination, not justified by general medical conditions or intellectual disability, leading to low performance in academic, school and daily life activities. Depending on the methodology used to select and classify the participants, studies have reported prevalences which vary from 1.4 to 15% among school age children, however high prevalences have been the result of studies which doesn't consider all diagnostic criteria, applying just a motor test to identify children with DCD. The goal of this study was to identify DCD in 7-year-old children, enrolled in public schools in the city of Araraquara-SP, by means of two assessment tools - motor test and a questionnaire for the parents; identify signs of Attention-Deficit/Hyperactivity Disorder (ADHD) by means of indirect evaluation; identify the prevalence of motor difficulties between genders and find the DCDQ-Brasil cutoff point by means of Receiver Operating Characteristic (ROC curve). It is a study with a quantitative, descriptive/exploratory approach. The sample was composed by 101 7-year-old schoolchildren, born between July, 2005 and January, 2006, enrolled in the city's public schools. Parents and guardians provided data on economic status, the child's performance in daily life, school and leisure activities and informed signs of ADHD, answering the following questionnaires (respectively): Critério de Classificação Econômica Brasil CPCEB; Developmental Coordination Disorder Questionnaire DCDQ Brasil; Swanson, Nolan and Pelham IV Scale - SNAP IV. The children were evaluated through Movement Assessment Battery for Children 2 MABC II. Descriptive analyses and statistical tests have been performed to verify the significance of the results. The economical statuses of the participants varied from B1 to D, representing no statistical significance. The combination of two assessment tools for DCD identification led to a 0.99% prevalence of children with severe DCD and a 2.97% prevalence of children with moderate DCD. The DCDQ-Brasil cutoff point found through the ROC curve was 49, increasing the prevalence of severe DCD to 2.97% and 4.95% for moderate DCD. Various levels of motor impairment have been identified, pointed out by the various scores of the children who presented DCD, and even though the prevalence was higher on boys, this result also did not present statistical significance. A direct correlation between signs of ADHD and moderate DCD was found, reinforcing the hypothesis of the existence of comorbidities, as well as the heterogeneity of motor difficulties demonstrated by children with DCD. This study represents one of the necessary steps in the caring for children with DCD - the identification, for further intervention referral, if necessary. It strengthens the importance of continuing investing in DCD studies in Brazil, as well as in the standardization of the DCDQ-Brasil cutoff point and the MABC-II validation for Brazilian children.